Theoretical study of the charge transport mechanism in π-stacked systems of organic semiconductor crystals. Issue 40 (29th September 2017) - Ya-Rui, Shi; Hui-Ling, Wei; Ya-Ting, Shi; Yu-Fang, Liu
Abstract : We investigate the influence of various factors on the charge transport mechanism. Abstract : In this study, the orientational dependence of the charge transport mechanism and some important factors related to crystal structure are systematically investigated by quantum chemical methods. Organic semiconductors with small reorganization energies and large transfer integrals originating from their π-stacking crystal structures show excellent charge transport properties. The reorganization energy from the geometrical relaxation occurs during the charge transfer process. The transfer integral of a molecular crystal should be attributed to multiple stacking parameters. A semi-classical simulation model to calculate the anisotropic mobility of a crystalline molecule is extended from one to three dimensions. As we predicted, the anisotropic mobility calculated from our model is improved by considering the contribution from every direction in space, rather than just one plane. This theoretical study determines the importance of tuning the molecular geometry and calculation accuracy for high-performance organic semiconductor materials.